Political Behavior - Layman, Geoffrey; Radcliff, Benjamin; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Political Behavior publishes original research in the general fields of political behavior, institutions, processes, and policies. Approaches include economic (preference structuring, bargaining), psychological (attitude formation and change, motivations, perceptions), sociological (roles, group, class), or political (decision making, coalitions, influence). Articles focus on the political behavior (conventional or unconventional) of the individual person or small group (microanalysis), or of large organizations that participate in the political process such as parties, interest groups, political action committees, governmental agencies, and mass media (macroanalysis). As an interdisciplinary journal, Political Behavior integrates various approaches across different levels of theoretical abstraction and empirical domain (contextual analysis). Officially cited as: Polit Behav.
Keywords: Political science; Sociology; Political Science; Sociology, general